Pupil Size in Relation to Cortical States during Isoflurane Anesthesia - Kum, Jeung Eun; Han, Hio-Been; Choi, Jee Hyun (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2016)
In neuronal recording studies on anesthetized animals, reliable measures for the transitional moment of consciousness are frequently required. Previous findings suggest that pupil fluctuations reflect the neuronal states during quiet wakefulness, whose correlation was unknown for the anesthetized condition. Here, we investigated the pupillary changes under isoflurane anesthesia simultaneously with the electroencephalogram (EEG) and electromyogram (EMG). The pupil was tracked by using a region-based active contour model. The dose was given to the animal in a stepwise increasing mode (simulating induction of anesthesia) or in a stepwise decreasing mode (simulating emergence of anesthesia). We found that the quickly widening pupil action (mydriasis) characterizes the transitional state in anesthesia. Mydriasis occurred only in the light dose in the emergence phase, and the events were accompanied by an increase of burst activity in the EEG followed by EMG activity in 47% of the mydriasis events. Our findings suggest that recording such pupil changes may offer a noncontact monitoring tool for indexing the transitional state of the brain, particularly when a lower threshold dose is applied.
Keywords: BURST-SUPPRESSION; ELECTROENCEPHALOGRAM; LAYER; INDEX